2022
DOI: 10.3390/molecules27062012
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Assessing the New Orally Disintegrating Tablets, Containing Nimodipine-hydroxypropyl-β-cyclodextrin and Nimodipine-methyl-β-cyclodextrin Inclusion Complexes

Abstract: The aim of the present study was to manufacture new orally disintegrating tablets containing nimodipine–hydroxypropyl-β-cyclodextrin and nimodipine–methyl-β-cyclodextrin inclusion complexes. For obtaining a better quality of the manufactured tablets, three methods of the preparation of inclusion complexes, in a 1:1 molar ratio, were used comparatively; namely, a solid-state kneading method and two liquid state coprecipitation and lyophilization techniques. The physical and chemical properties of the obtained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…The FTIR spectrum of pure AML shows the presence of its main characteristic peaks at 3552 cm −1 and 3592 cm −1 due to the N-H amine stretching vibration; at 2730 cm −1 assigned to the aliphatic C-H stretch; at 1689 cm −1 due to ester carbonyl C=O stretches; at 1602 cm −1 and 1477 cm −1 assigned to aromatic skeletal stretches and CH 3 , CH 2 bending, respectively; at 1262 cm −1 due to ester (C-O) asymmetric stretch; at 1207 cm −1 due to sulfonate (S=O) asymmetric stretch; at 1099 cm −1 due to aromatic C-Cl stretch; at 1039 cm −1 assigned to ether (C-O-C) symmetric stretch; and at 757 cm −1 due to aromatic (C-H) bending [ 38 ]. The FTIR spectrum of HP-β-CD showed characteristic bands that belonged to saccharides: 3400 cm −1 (O-H stretching vibration), 2927 cm −1 (C-H stretching vibration), 1641 cm −1 (O-H bending vibration), and 1033 (C-O bond vibration) [ 3 , 39 , 40 ]. The absorption peak found at 845 cm −1 is characteristic of an α-type glycosidic bond.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FTIR spectrum of pure AML shows the presence of its main characteristic peaks at 3552 cm −1 and 3592 cm −1 due to the N-H amine stretching vibration; at 2730 cm −1 assigned to the aliphatic C-H stretch; at 1689 cm −1 due to ester carbonyl C=O stretches; at 1602 cm −1 and 1477 cm −1 assigned to aromatic skeletal stretches and CH 3 , CH 2 bending, respectively; at 1262 cm −1 due to ester (C-O) asymmetric stretch; at 1207 cm −1 due to sulfonate (S=O) asymmetric stretch; at 1099 cm −1 due to aromatic C-Cl stretch; at 1039 cm −1 assigned to ether (C-O-C) symmetric stretch; and at 757 cm −1 due to aromatic (C-H) bending [ 38 ]. The FTIR spectrum of HP-β-CD showed characteristic bands that belonged to saccharides: 3400 cm −1 (O-H stretching vibration), 2927 cm −1 (C-H stretching vibration), 1641 cm −1 (O-H bending vibration), and 1033 (C-O bond vibration) [ 3 , 39 , 40 ]. The absorption peak found at 845 cm −1 is characteristic of an α-type glycosidic bond.…”
Section: Resultsmentioning
confidence: 99%
“…SEM images of Me-β-CD, the AML-Me-β-CD physical mixture, and AML-Me-β-CD complexes obtained using the kneading, coprecipitation, and lyophilization methods are shown in Figure 4 . Me-β-Cd presented fragments of spherical shell morphology ( Figure 4 a) [ 39 ]. By using different synthesis procedures, different morphologies were achieved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the clear mixture was freeze-dried for 24 h (Freeze dryer, SIM FD8-8T, SIM International, USA), and the dried CX was collected, weighed, and kept for further evaluation. A physical mixture of Hsd and SBE-β-CD was prepared in a 1:1 molar ratio by gently mixing the two components [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the same research, docking studies revealed that umbelliferone was not completely inserted into the α-CD cavity in all poses because of its small cavity size [9]. In the research studies of M. Novac et al [16] and F. Maestrelli et al [17], β-CD and various β-CD's derivatives (2-hydroxypropyl-β-cyclodextrin, (HP-β-CD), randomly methylated-β-CD (RAMEB), and sulfobutylether-β-CD (SBE-β-CD)), in the form of inclusion complexes with APIs such as nimodipine (calcium channel blocker [16]) and flufenamic acid (non-steroidal anti-inflammatory agent [17]), have been incorporated in pharmaceutical tablets via direct compression. The complexation of flufenamic acid with RAMEB remarkably improved its dissolution rate, being a useful tool for the effective Encapsulation is a common technique that is used to protect the encapsulated compounds from adverse environments, and to modify the physicochemical properties of different hydrophobic molecules such as their aqueous solubility and biological profile.…”
Section: Introductionmentioning
confidence: 92%